2014
DOI: 10.1136/tobaccocontrol-2013-051397
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco industry manipulation of data on and press coverage of the illicit tobacco trade in the UK

Abstract: BackgroundIn the UK, transnational tobacco companies (TTCs) have been arguing that levels of illicit trade are high and increasing and will rise further if standardised packaging is implemented. This paper examines trends in and accuracy of media reporting of, and industry data on, illicit tobacco in the UK.MethodsQuantification of the volume, nature and quality of press articles citing industry data on illicit tobacco in UK newspapers from March 2008 to March 2013. Examination of published TTC data on illicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 22 publications
1
77
0
Order By: Relevance
“…Searches generated ten relevant empirical studies 21,30,[32][33][34][35][36][37][38][39] : three were qualitative studies (two reporting focus group research with young adult smokers in Scotland 30,32 , and in-depth interviews with retailers in New Zealand 39 ); three were content analyses (of online commentary on tobacco packaging in Australia 33 , UK press coverage of the illicit tobacco trade 34 and the four TTC submissions to the consultation in the UK 35 ); two were cross sectional surveys (of illicit tobacco use following introduction of standardized packaging in Australia) 36,37 ; and two were before and after studies (one of availability of illicit tobacco in small retail outlets 38 and one empty-pack survey before and after the introduction of standardized packaging in Australia) 21 . See Table 2 for a summary of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Searches generated ten relevant empirical studies 21,30,[32][33][34][35][36][37][38][39] : three were qualitative studies (two reporting focus group research with young adult smokers in Scotland 30,32 , and in-depth interviews with retailers in New Zealand 39 ); three were content analyses (of online commentary on tobacco packaging in Australia 33 , UK press coverage of the illicit tobacco trade 34 and the four TTC submissions to the consultation in the UK 35 ); two were cross sectional surveys (of illicit tobacco use following introduction of standardized packaging in Australia) 36,37 ; and two were before and after studies (one of availability of illicit tobacco in small retail outlets 38 and one empty-pack survey before and after the introduction of standardized packaging in Australia) 21 . See Table 2 for a summary of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…There were few studies examining tobacco standardized packaging and illicit trade and those that were available were generally not of high quality. We identified ten relevant empirical studies which examined standardized packaging and illicit tobacco 21,30,[32][33][34][35][36][37][38][39] . Five studies reported smokers did not intend to 30,32 or actually 21,36,37 purchase more illicit tobacco following standardized packaging although one 33 suggested a small number of responders to online news felt smokers In 179 (59%) of the shops the secret shopper then asked the retailer about the availability of unbranded, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tobacco industry argues against many tobacco control measures, including tobacco tax increases and standardized packaging, on the basis that such initiatives increase illicit trade of tobacco products 7, 8.…”
Section: Introductionmentioning
confidence: 99%